2023
DOI: 10.1002/anie.202308048
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Wagner–Meerwein Rearrangements with Concomitant Nucleophilic Hydrofluorination

Reece H. Hoogesteger,
Nicola Murdoch,
David B. Cordes
et al.

Abstract: We report a cobalt‐catalyzed Wagner–Meerwein rearrangement of gem‐disubstituted allylarenes that generates fluoroalkane products with isolated yields up to 84 %. Modification of the counteranion of the N‐fluoropyridinium oxidant suggests the substrates undergo nucleophilic fluorination during the reaction. Subjecting the substrates to other known metal‐mediated hydrofluorination procedures did not lead to observable 1,2‐aryl migration. Thus, indicating the unique ability of these cobalt‐catalyzed conditions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Optimization of the enantioselective semipinacol rearrangement Previously we have shown that this approach is viable for conducting Wagner−Meerwein rearrangements that involve a 1,2-aryl migration. [48] These studies unveiled a phenonium ion as a probable intermediate with subsequent regioselective nucleophilic fluorination finalizing the relocation process. Thus, given this reactivity, we postulated that a hydro-semipinacol rearrangement involving a 1,2-aryl shift was viable.…”
Section: Resultsmentioning
confidence: 98%
“…Optimization of the enantioselective semipinacol rearrangement Previously we have shown that this approach is viable for conducting Wagner−Meerwein rearrangements that involve a 1,2-aryl migration. [48] These studies unveiled a phenonium ion as a probable intermediate with subsequent regioselective nucleophilic fluorination finalizing the relocation process. Thus, given this reactivity, we postulated that a hydro-semipinacol rearrangement involving a 1,2-aryl shift was viable.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, running the reaction in an NMR tube increased the yield to 60%, likely as a result of enhanced light penetration. Interestingly, for limonene (14) bearing two different types of alkenes, the catalyst was highly selective for the hydrofluorination of the terminal alkene, giving product 14−1 in 34% yield with only 2% speculative hydrofluorination of the internal alkene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Activation methods include the use of strong acids, highly oxidizing photocatalyst, and the combination of electrochemistry and palladium catalysis . Most recently, Johnston and co-workers reported a Co­(salen)-catalyzed alkene hydrofluorination reaction involving a 1,2-aryl shift using a combination of a hydrosilane and BF 4 – as reagents . These methods, while significantly expanding the toolbox for hydrofluorination reactions, are sensitive to the substitution patterns of alkenes; thus, these transformations are limited to a certain type of alkene (e.g., styrenes or 1,1-disubstituted alkenes).…”
Section: Introductionmentioning
confidence: 99%